Seismic precast. Seismic performance assessment of existing precast industrial buildings - Furtado, André (2021)
Past seismic events exposed important fragilities in precast reinforced concrete buildings and highlight the need to undertake measures to mitigate future losses.The study presented identify potential structural and nonstructural fragilities of the Portuguese building stock and provide guidance to reduce the associated direct and indirect socio-economic impact